Effect of pre-hoop expansion deformation on the tensile and fatigue properties of zirconium plate - Haidong Qi; Xiping Song (Journal of Materials Research and Technology)
The effect of the pre-hoop expansion deformation on the tensile and fatigue properties of zirconium plate has been investigated. The results showed that with the increase of the pre-hoop expansion deformation, the yield and ultimate strength increased linearly but the elongation decreased linearly, while the fatigue life first increased, and decreased when the pre-hoop expansion deformation exceeded 10%. The microstructure showed that after tensile and fatigue deformation, the orientation of {0001} crystal plane changed from the ND to the RD and TD, and with the increase of pre-hoop expansion deformation, these changes enhanced. The hardness results showed that there existed a work hardening zone around the center-hole of specimens. The stress field simulation showed that after the pre-hoop expansion deformation, there existed a compressive stress, a stress-free zone and a tensile stress around the center-hole of specimens. And the compressive stress gradually changed to tensile stress with the increase of tensile deformation. Fracture surfaces showed that all cracks initiated at the inner side of the narrow edge of specimens. With the pre-hoop expansion deformation increasing, the necking degree and the dimple depth of tensile fracture surface decreased, while the fatigue crack initiation changed from a single crack to multiple cracks. The work hardening and compressive stress offered positive effects on the tensile and fatigue properties, while the tensile stress offered negative effects on the fatigue property. A multiple dislocation interaction mode was proposed to explain the strengthening mechanism of tensile and fatigue deformation under the pre-hoop expansion deformation.